Penerapan Perencanaan Pajak PPh Pasal 21 Karyawan Tetap Menggunakan Metode Gross Up, Gross, Net Sebagai Upaya Penghematan Beban Pajak Penghasilan Pasal 25 Pada CV. ANARA Kota Kediri - Selvi Mayranti dewi; Khasanah Sahara; Imarotus Suaidah (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This research is motivated by the government policy changes in 2021, which involve the amendment of Income Tax Article 21 rates from four tiers to five tiers. The purpose of this study is to determine the most effective method in minimizing the income tax burden under Article 25 for CV.Anara. This research utilizes primary data and employs quantitative descriptive analysis techniques as well as the Gross Up, Gross, and Net Method analysis tools. The results of this study indicate that the most efficient method is the Gross Up Method, as providing allowances results in efficiency in Corporate Income Tax (CIT) under Article 25. Consequently, the company can pay lower CIT compared to the Gross and Net Methods. Based on the analysis conducted, the Gross Up Method can save CIT payments. With a modest profit margin, this method minimizes the tax burden for the company. The implementation of the Gross Up Method for Article 21 CIT can also boost employee productivity. These findings align with previous research conducted by Khairani & Alistraja Dison Silalahi in 2022, Khoiriawati & Meirini in 2022, and Muhammad Yahya Malik & Khasanah Sahara in 2023, which show that the Gross Up Method is the most effective approach to minimize income tax burdens. Additionally, applying tax planning for zakat and donations can further reduce the tax burden on the company. This research utilizes the latest tax rates with five tiers, following the most recent regulations.